Fecal microbiota transplantation in the treatment of Clostridium difficile infection: state of the art and literature review - MESSIAS,BRUNO AMANTINI (2018)
ABSTRACT Clostridium difficile infection is a common complication following intestinal dysbiosis caused by abusive antibiotic use. It presents medical importance due to the high rates of recurrence and morbidity. Fecal microbiota transplantation is an effective alternative for the treatment of recurrent and refractory C. difficile infection and consists of introducing the intestinal microbiota from a healthy donor into a patient with this infection. The exact physiological mechanism by which fecal microbiota transplantation alters the intestinal microbiota is not well established, but it is clear that it restores the diversity and structure of the microbiota by promoting increased resistance to colonization by C. difficile. Several routes of transplant administration are being studied and used according to the advantages presented. All forms of application had a high cure rate, and the colonoscopic route was the most used. No relevant complications and adverse events have been documented, and the cost-effectiveness over conventional treatment has proven advantageous. Despite its efficacy, it is not commonly used as initial therapy, and more studies are needed to establish this therapy as the first option in case of refractory and recurrent Clostridium difficileinfection.